Certain aspects of uncoupling due to mitochondrial uncoupling proteins in vitro and in vivo - Dlasková, Andrea; Špaček, Tomáš; Skobisová, Eva; Šantorová, Jitka; Ježek, Petr (Biochimica et biophysica acta, 2006)
Thermogenic uncoupling has been proven only for UCP1 in brown adipose tissue. All other isoforms of UCPs are potentially acting in suppression of mitochondrial reactive oxygen species (ROS) production. In this contribution we show that BAT mitochondria can be uncoupled by lauric acid in the range of approximately 100 nM when endogenous fatty acids are combusted by carnitine cycle and beta-oxidation is properly separated from the uncoupling effect. Respiration increased up to 3 times when related to the lowest fatty acid content (BSA present plus carnitine cycle). We also illustrated that any effect leading to more coupled states leads to enhanced H2O2 generation and any effect resulting in uncoupling gives reduced H2O2 generation in BAT mitochondria. Finally, we report doubling of plant UCP transcript in cells as well as amount of protein detected by 3H-GTP-binding sites in mitochondria of shoots and roots of maize seedlings subjected to the salt stress.
Keywords: Plant Shoots; oxidační stres; Mitochondria; guanosintrifosfát; Uncoupling Agents; Guanosine Triphosphate; vazebná místa; Mammals; reaktivní formy kyslíku; Cell Respiration; mastné kyseliny; výhonky rostlin; buněčné dýchání; membránové proteiny; kukuřice setá; Plant Roots; techniky in vitro; Membrane Proteins; peroxid vodíku; iontové kanály; kyseliny laurové; Fatty Acids; Plant Proteins; Hydrogen Peroxide; mitochondriální proteiny; kořeny rostlin; Carnitine; Zea mays; Ion Channels; hnědá tuková tkáň; Carrier Proteins; savci; Binding Sites; Mitochondrial Proteins; Reactive Oxygen Species; rozpřahující látky; Animals; karnitin; zvířata; Financing, Organized; Oxidative Stress; financování organizované; Adipose Tissue, Brown; transportní proteiny; mitochondrie; In Vitro Techniques; Lauric Acids; rostlinné proteiny